2016
DOI: 10.3945/jn.116.236000
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation with α-Ketoglutarate Activates mTOR Signaling and Enhances Energy Status in Skeletal Muscle of Lipopolysaccharide-Challenged Piglets

Abstract: Dietary AKG supplementation activated mTOR signaling, inhibited ACC-β, and improved energy status in skeletal muscle of LPS-challenged piglets. These results provide a biochemical basis for the use of AKG to enhance piglet growth under inflammatory or practical postweaning conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 57 publications
4
32
0
Order By: Relevance
“…The AKG doses were selected based on the combination of several articles (Chen et al, 2017;Wang et al, 2016). The three treatment groups were the low-protein diet supplemented with 0.5% (LP + 0.5%A), 1.0% (LP + 0.5%A) and 1.5% AKG (LP + 0.5%A).…”
Section: Experimental Dietsmentioning
confidence: 99%
See 3 more Smart Citations
“…The AKG doses were selected based on the combination of several articles (Chen et al, 2017;Wang et al, 2016). The three treatment groups were the low-protein diet supplemented with 0.5% (LP + 0.5%A), 1.0% (LP + 0.5%A) and 1.5% AKG (LP + 0.5%A).…”
Section: Experimental Dietsmentioning
confidence: 99%
“…Furthermore, Wang et al (2016) found that AKG has been added to the diet of animals to alleviate the phenomenon that IGF-1 content decreases in the blood caused by LPS stimulation. LP, low protein; LP + 0.5%A, low-protein diet supplemented with 0.5% AKG; LP + 1.0%A, low-protein diet supplemented with 1.0% AKG; LP + 1.5%A, low-protein diet supplemented with 1.5% AKG.…”
Section: Consequently Akg Promotes N Depositions In Cells Throughoutmentioning
confidence: 99%
See 2 more Smart Citations
“…Concentrations of biochemical parameters such as aspartate transaminase (AST), alanine transaminase (ALT), alkaline phosphatase (ALP), creatine kinase (CK), blood urea nitrogen (BUN), total bilirubin (TBIL), cholesterol (CHOL) and creatinine in plasma were measured with corresponding kits using a Hitachi 7060 Automatic Biochemical Analyzer (Hitachi, Japan) (23). D-xylose in plasma was determined as described by Hou et al (17).…”
Section: General Study Protocolmentioning
confidence: 99%